2011
DOI: 10.1007/s00423-011-0798-3
|View full text |Cite
|
Sign up to set email alerts
|

Ranking of patient and surgeons' perspectives for endpoints in randomized controlled trials—lessons learned from the POVATI trial [ISRCTN 60734227]

Abstract: Patients and surgeons did not differ in ranking predetermined outcomes in the POVATI trial. Only the variable "cosmetic result" is significantly more important from the surgeon's than from the patient's perspective. Ranking of outcomes might be a beneficial tool and can be a proper addition to RCTs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Most studies ( n = 19) included patients only, including preferences of pregnant women and parents of children (as proxies) . Five studies compared preferences of patients with those of healthcare professionals . One study compared preferences of primary stakeholders as patients, family members or mental healthcare providers with preferences of policymakers in schizophrenia .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies ( n = 19) included patients only, including preferences of pregnant women and parents of children (as proxies) . Five studies compared preferences of patients with those of healthcare professionals . One study compared preferences of primary stakeholders as patients, family members or mental healthcare providers with preferences of policymakers in schizophrenia .…”
Section: Resultsmentioning
confidence: 99%
“…Twenty‐eight studies compared preferences of different participant groups, mostly patients vs. health care professionals. Among the 22 studies evaluating preferences of patients and health care providers, only one stated that the preferences assessed were identical, and four found at least some agreement concerning the most valued outcomes . The remaining 17 studies showed differences between the groups studied, either in differing hierarchies or in strength of preferences.…”
Section: Resultsmentioning
confidence: 99%
“…To avoid any potential of predicting group allocation for patients, the block length is fixed in a separate document that is withheld from the study site. As performed in previous studies, sealed and opaque envelopes are produced and labeled with the randomization number containing a data sheet that states the group allocation for the patient with the respective randomization number [17-19]. Randomization envelopes will be used in consecutive order.…”
Section: Methods and Designmentioning
confidence: 99%
“…Since patients do not recall the smaller incision, we should ask ourselves whether surgeons and industry care more than do the patients to whom we offer SILS [71]. This observation is supported by a large RCT [72] where both surgeons and patients were preoperatively and postoperatively asked to rank predetermined, outcome variables hierarchically according to their importance. It was found "Cosmetic result" was the only variable being significantly more important from the surgeon's perspective than from the patient's perspective.…”
Section: Methodological Righteousness Sans Honestymentioning
confidence: 99%